Kinetic characteristics of barefoot running - Freedman, J. A.; Dufek, J. S.; Mercer, J. A. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
In spite of extensive research, as well asadvances in shoe development, runners continue to be injured at similar rate to those of 25 years ago. It has been hypothesized that shoes may actually contribute to injury rates by blocking plantar sensory information. Preliminary research has shown that the kinetics and kinematics during running barefoot are different from running in shoes, yet this research has constrained runners to a heel-toe running pattern both barefoot and in shoes. Therefore the purpose of this study was to compare impact characteristics between barefoot and shod running when footstrike is not constrained as well as to compare impact characteristics of barefoot running with a heel-toe running pattern to barefoot running with no constraints on footstrike.